Fasting regulates EGR1 and protects from glucose- and dexamethasone-dependent sensitization to chemotherapy - Di Biase, Stefano; Shim, Hong Seok; Kim, Kyung Hwa; Vinciguerra, Manlio; Rappa, Francesca; Wei, Min; Brandhorst, Sebastian; Cappello, Francesco; Mirzaei, Hamed; Lee, Changhan; Longo, Valter D (PLoS biology, 2017)
Fasting reduces glucose levels and protects mice against chemotoxicity, yet drugs that promote hyperglycemia are widely used in cancer treatment. Here, we show that dexamethasone (Dexa) and rapamycin (Rapa), commonly administered to cancer patients, elevate glucose and sensitize cardiomyocytes and mice to the cancer drug doxorubicin (DXR). Such toxicity can be reversed by reducing circulating glucose levels by fasting or insulin. Furthermore, glucose injections alone reversed the fasting-dependent protection against DXR in mice, indicating that elevated glucose mediates, at least in part, the sensitizing effects of rapamycin and dexamethasone. In yeast, glucose activates protein kinase A (PKA) to accelerate aging by inhibiting transcription factors Msn2/4. Here, we show that fasting or glucose restriction (GR) regulate PKA and AMP-activated protein kinase (AMPK) to protect against DXR in part by activating the mammalian Msn2/4 ortholog early growth response protein 1 (EGR1). Increased expression of the EGR1-regulated cardioprotective peptides atrial natriuretic peptide (ANP) and B-type natriuretic peptide (BNP) in heart tissue may also contribute to DXR resistance. Our findings suggest the existence of a glucose-PKA pathway that inactivates conserved zinc finger stress-resistance transcription factors to sensitize cells to toxins conserved from yeast to mammals. Our findings also describe a toxic role for drugs widely used in cancer treatment that promote hyperglycemia and identify dietary interventions that reverse these effects.
Keywords: Fasting; Cyclic AMP-Dependent Protein Kinases; dexamethason; fyziologický stres; metformin; Diet; protein 1 časné růstové odpovědi; Cardiotoxins; natriuretický peptid typu B; Female; Cytoprotection; Metformin; Antineoplastic Agents; Atrial Natriuretic Factor; proteinkinasy aktivované AMP; cytoprotekce; zvířata; myši; glukosa; myši inbrední C57BL; hyperglykemie; AMP-Activated Protein Kinases; časové faktory; Mice; Stress, Physiological; Hyperglycemia; ženské pohlaví; Early Growth Response Protein 1; dieta; atriální natriuretický faktor; Dexamethasone; Glucose; Mice, Inbred C57BL; protinádorové látky; omezení příjmu potravy; proteinkinasy závislé na cyklickém AMP; Animals; Natriuretic Peptide, Brain; Time Factors; kardiotoxiny